(untitled) (Journal of the College of Basic Education, 2022)
This research includes the development of a self-tracking system for solar concentrators which can increase the gained solar energy.This system is specified by using the generated power from the solar cells to feed the tracking system directly. In other words the electrical power needed is self generated.Therefore, this system can be used in agricultural placesin our country.The other side of the work in this research is using advanced technique for tracking the solar collectors. The design combines a Field Programmableprocessor with two-axis motor tracking controller to integrate such as microprocessor, memory, and input/output into one Altera Field Programmable based on system-on-programmable-chip concepts.